ANALISIS PERKEMBANGAN KEMAMPUAN KEUANGAN DAERAH DALAM MENDUKUNG PELAKSANAAN OTONOMI DAERAH PADA DINAS PENDAPATAN DAERAH KOTA TIDORE - Alting, Umilhair; Pontoh, Winston; Suwetja, I Gede (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Fiscal decentralization is one the major component of the decentralization implementation of regional autonomy. As the new beginning in regional development and the people in managing the resources or all of the potential to the prosperity and the progress of region. Financial aspect is one of the basic criteria to find out the real capability regional government in managing their autonomy system (household system) the capability of regional government in managing their financial can be seen in APBD which describes the capability of local government in financing the activities of development task and equity in each region. The purpose of this research is to determine the financial capability of Tidore in regional autonomy especially in 2013-2017 judging by ratio of independency, decentralization fiscal degree, growth ratio. This research used observation, interview and documentation to collect the data. The data was analyzed using qualitative and quantitative data with described analysis. The result showed that the independence ratio of Tidore has been able to improve its financial capability. The degree of decentralization is still highly dependent on the central government, although it has been increasing year by year. Growth rate fluctuated this indicates the local government of Tidore is not too concerned with regional development and community welfare.Keywords: regional autonomy, ratio of independency, The degree of decentralization ratio, Growth ratio.